Malala: the story of a Muslim girl and a Muslim nation. Issue 3 (4th May 2019) - Khurshid, Ayesha; Pitts, Brittany
ABSTRACT: In this article, we analyze the coverage of Malala in The New York Times and The Wall Street Journal to explore how these influential media sources characterize Islam and Pakistan to tell Malala's story. Our discourse analysis reveals how these newspapers construct Malala's status as a global icon as an embodiment of her subject position as a girl. This media discourse mobilizes Malala's agency in relation to her potential as an individual whereas her vulnerability as a young girl is presented in reference to her Muslim heritage and culture. Malala's image as a global icon, thus, is produced through approaching her as an agent in a culture where girls are vulnerable victims of patriarchy. Through focusing on this media discourse, this article argues that Malala's image as a global icon of girls' education has become a site to reinsert, rather than challenge, the dominant images about Islam and Muslim societies.